Implementation of Fuel Subsidy Policy and Its Implications for the State Budget - Ferdy Lukman Jaylani; Yulianah Yulianah; Muhamad Zahwan Pratama; Nayla Nazwa Putri; Rahma Alia Nurvadillah; Gunawan Gunawan (Advances in Community Services Research, 2026)
Purpose: This study evaluates the implementation of fuel subsidy policies in Indonesia and examines their implications for the sustainability of the State Budget (APBN) from the perspectives of fiscal efficiency and social protection. Research Method: A descriptive qualitative approach was employed using documentation studies and literature review. Data were collected from official government documents, including APBN Financial Notes, Central Government Financial Reports (LKPP), BPK audit reports, fuel subsidy regulations, and empirical studies published between 2022 and 2025. Data were analyzed inductively using Mazmanian and Sabatier's policy implementation framework. Results and Discussion: The findings indicate that fuel subsidy implementation remains constrained by targeting inaccuracies, institutional limitations, unequal digital access, and vulnerability to fluctuations in global oil prices and exchange rates. The effectiveness of digital monitoring systems and quota mechanisms depends on institutional readiness, data quality, and inter-agency coordination. Implications: Strengthening beneficiary databases, institutional coordination, and fiscal governance is essential for improving subsidy effectiveness and sustainability. Originality: This study operationalizes Mazmanian and Sabatier's framework to explain how legal structures, institutional capacity, target-group characteristics, and external conditions shape the implementation of fuel subsidies in Indonesia.